From Rural Marginality To Urban Marginality - Román, Manuel (1977)
Few Third World countries do not experience a migration process. The reason is the apparent dependence of rural life over urban life, which reproduces part of the behavioral models (at economic and social relations, culture, values, etc.) that characterize relations between developed and underdeveloped. But in the case of the third world, these movements, which are typical of the population dynamics, are primarily due to differences between the levels of city life and country.